If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-1 + 2x) = 76 (-1 * 4 + 2x * 4) = 76 (-4 + 8x) = 76 Solving -4 + 8x = 76 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 8x = 76 + 4 Combine like terms: -4 + 4 = 0 0 + 8x = 76 + 4 8x = 76 + 4 Combine like terms: 76 + 4 = 80 8x = 80 Divide each side by '8'. x = 10 Simplifying x = 10
| -4x-7=-3x-2 | | w=95+28 | | 3k-5=-26 | | .2t+14.7=3.1 | | 5x^2+10=-50 | | (b+25)+3b=435 | | 1+2x+5y=12 | | .25+7.5=12.75 | | 8(x+3)+5=-35 | | -8k+ar=r-5y | | p=lrt(t) | | .7x+x=952 | | -164=-2-6(-6p+3) | | -100y+30=120+90 | | 28-5x=16+7x | | -19n-20=20-14n-13n | | 1a+4-8a=-10 | | 5(5-6x)=-125 | | -4+2c=0 | | (x-1)squared=16 | | -3x-24+2x+13=-3 | | -4u^2-17u-15= | | 60/-220= | | -4+2=0 | | 6-8x=7x-9x+0 | | 10x+7=9x-3 | | Y=-6(0)+2 | | 11x+14+5=180 | | 5x-(6-x)=2x-22 | | 15(6x+2)=10(4x+70) | | 9(2x+3)-5=-(x-3) | | 10x^2-1=3x |